Radiocarbon datings of planktic foraminifer samples from gravity core LV28-34-2 - Dirk Nürnberg (PANGAEA, 2025)
Bound by the Asian continent to the northwest and north and the Kurile-Kamchatka-Island Arc to the east and southeast, the Sea of Okhotsk is the second largest marginal sea of the Pacific. In view of strengthened efforts of better understanding cool climate dynamics, the Sea of Okhotsk became an increasing focus of interest as it plays a key role for the modern hydrology of the NW Pacific, its high primary productivity, and its pronounced seasonality in sea ice coverage. We here provide proxydata from gravity core LV28-34-2. The ~9.6 m-long core was recovered from the Derugin Basin in the northern Sea of Okhotsk (53°51.971 N 146°47.499 E) from 1431 m water depth during R/V Lavrentiev Cruise LV28 in 1998 (doi:10.3289/GEOMAR_REP_82_1999). The proxyrecords cover the last ~150 kyrs at centennial resolution. The dataset comprises 8 Accelerator Mass Spectrometry (AMS) radiocarbon (14C) ages obtained from sediment core LV28-34-2, measured by the extquotesingleLeibniz-Labor für Altersbestimmung und Isotopenforschung Kiel extquotesingle, https://www.leibniz.uni-kiel.de. The AMS14C ages were measured on samples of mixed planktic calcitic foraminifera and benthic molluscs. The raw radiocarbon ages were calibrated to calender years using the software Calib 6.0 and a constant reservoir age correction of 800 yrs following Nürnberg et al. (2011).